Ketersediaan Air Bagi Kehidupan: Studi Terhadap Asal-Usul dan Hilangnya Air di Bumi Perspektif Al-Quran dan Sains - Musarofah, Siti (Ngabari: Jurnal Studi Islam dan Sosial, 2021)
The water on this earth seems to never run out even though humans use it continuously. However, sometimes the water on the surface of the earth is lost so that the earth looks dry. This study aims to find out where the water on earth comes from and where it is lost according to the perspective of the Qur'an and science. By using the literature study method, the researchers found: 1) according to the view of the Qur'an, water on earth comes from the sky in the form of rain, while according to science there is a possibility that water on earth comes from ice in the asteroid belt that fell to earth. 2) Water on earth can undergo evaporation and freezing depending on weather conditions. This is what causes a place on earth to experience drought or lack of water. Knowledge of the origin and loss of water on earth will be useful for people's lives in responding to water use as wisely as possible.